2018
DOI: 10.25134/ieflj.v4i2.1375
|View full text |Cite
|
Sign up to set email alerts
|

The Varieties of Homework Given by English Teachers of Vocational Schools

Abstract: Learning inside the classroom is never enough because there are various limitations, so it needs the non-school hour assignment called homework. This research aims to find out the varieties of homework given by English teachers of vocational schools. This research uses a qualitative descriptive method by involving eight English teachers of vocational schools in Yogyakarta. Open-ended questionnaires, interview, and document analysis are used to collect the data. In analyzing the obtained data, the researcher do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…As time spent in class is limited, complementary learning methods outside of the classroom may be required to ensure proper learning by students (Nunan & Richards, 2014). Homework has been shown to have numerous beneficial effects such as consolidating learning from the classroom, broadening and sharpening language skills, and fostering self-regulation and self-efficacy (Amiryousefi, 2016;Azizah, 2018;Kominato, 2016;MacDonald, 2017;Ramdass & Zimmerman, 2011). This is of particular importance to EFL students, who often lack a sense of security when they are required to write in a language other than their L1 (Abadikhah et al, 2018).…”
Section: Homeworkmentioning
confidence: 99%
See 1 more Smart Citation
“…As time spent in class is limited, complementary learning methods outside of the classroom may be required to ensure proper learning by students (Nunan & Richards, 2014). Homework has been shown to have numerous beneficial effects such as consolidating learning from the classroom, broadening and sharpening language skills, and fostering self-regulation and self-efficacy (Amiryousefi, 2016;Azizah, 2018;Kominato, 2016;MacDonald, 2017;Ramdass & Zimmerman, 2011). This is of particular importance to EFL students, who often lack a sense of security when they are required to write in a language other than their L1 (Abadikhah et al, 2018).…”
Section: Homeworkmentioning
confidence: 99%
“…As a strategy for potentially mitigating writing anxiety among students, instructors at all levels of education have used homework as an out-of-class task to reinforce learning beyond the classroom (Azizah, 2018;Kominato, 2016;MacDonald, 2017). It has been reported that there is a strong, consistent positive correlation between students' academic achievement and the time they spend on homework (Carr, 2013).…”
Section: Introductionmentioning
confidence: 99%